2014
DOI: 10.1146/annurev-economics-080213-041238
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Revealed Preference

Abstract: This article aims to provide an introduction to empirical revealed preference (RP) and an overview of the current state of the field. We hope to give a sense of how RP methods work and the types of questions they can address and to assess the strengths and drawbacks of the approach. After briefly recapping the basics of RP theory, we review and critically assess the literature in two main areas representing the principal fields in which recent research has made significant advances: broadening the scope of RP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 83 publications
0
23
0
Order By: Relevance
“…11 For reviews of this literature, see, for example, Varian (2005), Cherchye, Crawford, De Rock, andVermeulen (2009), andDe Rock (2014). 12 Much of the work in this strand contemplates individual, static choice, and linear budget sets.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…11 For reviews of this literature, see, for example, Varian (2005), Cherchye, Crawford, De Rock, andVermeulen (2009), andDe Rock (2014). 12 Much of the work in this strand contemplates individual, static choice, and linear budget sets.…”
Section: Related Literaturementioning
confidence: 99%
“…In related work, researchers pursue revealed preference tests for intertemporal choice (e.g., Browning (1989)), nonlinear budget sets (e.g., Matzkin and Richter (1991)), market data (e.g., Brown and Matzkin (1996)), and collective choice (e.g., Chiappori (1988), Cherchye, De Rock, and Vermeulen (2007)). This work is surveyed by Crawford and De Rock (2014). 13 We take a nonparametric approach with respect to the probability distortion function, which is the object of our primary interest.…”
Section: Related Literaturementioning
confidence: 99%
“… 3 We refer the reader to Crawford and De Rock (2014), who provide a comprehensive review of the literature on revealed preference methods, including how GARP can be tested empirically. …”
mentioning
confidence: 99%
“…We refer the reader toCrawford and De Rock (2014), who provide a comprehensive review of the literature on revealed preference methods, including how GARP can be tested empirically.© 2015 The Authors. The Economic Journal published by John Wiley & Sons Ltd on behalf of Royal Economic Society.…”
mentioning
confidence: 99%
“…In this paper, we focus on algorithmic results concerning tests of rational behavior in consumer choice settings. For different discussions of the topic, we refer the reader to the recent monograph on the theory of revealed preference by Chambers and Echenique (2016), and to a survey by Crawford and De Rock (2014) on empirical revealed preference; an earlier overview can be found in Houtman (1995). Finally, we should note that certain aspects of revealed preference theory, as a way of explaining choice behavior, have also been criticized; see, e.g., the works of Hausman (2000) and Wong (2006).…”
Section: Motivationmentioning
confidence: 99%